Acetamiprid, chlorantraniliprole, and in some situations the physical barriers MultiPro® or Kvaae® wax, can be alternatives to traditional synthetic pyrethroid insecticides for the protection of young conifers from damage by the large pine weevil Hylobius abietis L. Issue 4 (19th May 2021) - Moore, Roger; Willoughby, Ian H.; Moffat, Andrew J.; Forster, Jack
ABSTRACT: In UK forestry, the synthetic pyrethroid insecticides alpha-cypermethrin and cypermethrin have been used for many years to provide protection for young trees from damage by the large pine weevil, Hylobius abietis L. However, concerns over the toxicity of these insecticides has led to a search for alternatives. In our work, applications of 0.037 g.a.i.stem –1 acetamiprid provided high levels of protection from Hylobius browsing, comparable to alpha-cypermethrin or cypermethrin, and without causing phytotoxicity. However, re-application is likely to be required in the second growing season after planting. Our research identified that acetamiprid treated trees can be safely cold stored as part of normal nursery practice. Acetamiprid is less toxic than synthetic pyrethroids. We also found that pre-treating trees with 0.016 g.a.i.stem –1 chlorantraniliprole, a relatively low toxicity insecticide, can be equally effective in protecting trees, and that dye markers can be safely used to help target spays. Our testing of physical barriers such as MultiPro®, and to a lesser extent Kvaae® wax, suggests they may have a role as a partial substitute for the use of insecticides in some circumstances in the UK and Ireland, but only as part of an integrated approach where on-site populations of Hylobius are predicted to be low.